2018
DOI: 10.1163/22134468-00603001
|View full text |Cite
|
Sign up to set email alerts
|

TRF1: It Was the Best of Time(s)…

Abstract: This is an open access article distributed under the terms of the prevailing CC-BY license at the time of publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 80 publications
1
2
0
Order By: Relevance
“…To estimate whether confidence distorts duration judgments, physically and mentally healthy individuals were tested. Verifying previous findings 15,16 , we demonstrated that the perceived duration of the monetary gain condition was perceived as longer than the neutral condition and that confidence, as the perceived likelihood of being correct, was higher in a monetary gain scenario than in neutral and loss scenarios. We found that individual differences in confidence influenced duration judgments.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…To estimate whether confidence distorts duration judgments, physically and mentally healthy individuals were tested. Verifying previous findings 15,16 , we demonstrated that the perceived duration of the monetary gain condition was perceived as longer than the neutral condition and that confidence, as the perceived likelihood of being correct, was higher in a monetary gain scenario than in neutral and loss scenarios. We found that individual differences in confidence influenced duration judgments.…”
Section: Introductionsupporting
confidence: 89%
“…However, it has also been reported that when there is a potential to win money, the duration is perceived as longer than in loss or neutral conditions. In other words, cuing a monetary reward prior to a duration judgment task distorts time, causing it to be overestimated compared to the reference duration 16 . Given the aforementioned different monetary reward conditions, a considerable body of literature generally associates attentional [17][18][19][20][21][22] or intentional [23][24][25][26] resources with monetary gain, which causes a longer perception of duration.…”
Section: Introductionmentioning
confidence: 99%
“…They achieved greater precision and accuracy of 92.06% by combining multimode magnetic resonance with the CNN core. Gunawardena et al in [26] utilized 1615 complete brain MRI scans for the diagnosis of AD. At first, they employed the existing vector carrier method for detecting AD with an accuracy of 84.4%.…”
Section: B Convolutional Neural Network Basedmentioning
confidence: 99%